(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
The paper presents the results from a study of the possibility to use Bilberries anthocyanins as a corrosion inhibitor for aluminum alloy EN AW-2024 in 1 М solution of HCl. In this study the model system between Bilberries anthocyanins and metal was investigated. The inhibitory effect of Bilberries anthocyanins on the corrosion of aluminum alloy EN AW-2024 in 1M HCl was investigated by electrochemical methods and mathematical analysis to validate the results. The absorption was determined from 25 oC. The results show that Bilberries anthocyanins exhibits a good inhibitory effect on the corrosion of the aluminium alloy EN AW-2024 in 1M HCl. The reason for the good inhibitory effect is the adsorption of the inhibitor molecules on the surface of the aluminum alloy.